Sinergismo entre química e matemática: ensino de planejamento fatorial nos cursos de graduação e pós-graduação em química da UFSCar - Pereira Filho, Edenir Rodrigues (2022)
The main idea of this dissertation is to highlight the synergism of two sciences: chemistry and mathematics. The first part of the text is dedicated to a chemometric tool known as Design of Experiments (DoE) applied to the optimization of mixtures. The optimization of an etching process was discussed, and mixtures composed of three acids were evaluated for semicondutors surface treatment. Two strategies were assessed: (i) the use of partial derivate and (ii) the implementation of an algorithm to determine the optimal experimental condition. During the application of partial derivative, several aspects need to be analyzed to identify if the optimal point is located at the vertice, edge, or inner part of the mixture (triangle). On the other hand, the proposed algorithm employed successive approximations avoiding the application of several exception conditions as demonstrated in partial derivative strategies. The proposed algorithm creates an initial population of variables combination (v1, v2, ..., vn) and tests it in order to identify the best condition. The second part of the dissertation, it was performed a comparison between undergraduate and graduate students from chemistry courses. Both groups of students (n = 200) had classes about DoE, and two types of data were considered: (i) students’ grades obtained during the evaluations and (ii) students’ opinions about the course. This comparison was performed before and during the pandemic of Covid-19. During the pandemic period, it was prepared videos about several topics related to DoE and these videos were presented to the students using the YouTube platform. In addition, recorded synchronous meetings were also performed. The recorded material (≈ 20 hours) was watched for more than 2500 hours. Before the pandemic period, it was not observed any difference between both groups of students regarding the grades obtained. On the other hand, the students’ opinion pointed differences (p − value < 0.05): aspects about the remote classes (i) before and (ii) during the pandemic. It was observed that the graduate students are more interested and open to the strategies of remote classes than the undergraduate. Approximately 60% of the graduate students are open to hybrid classes after the pandemic. The experience with remote classes permitted to reach students from different parts of Brazil (17 states) as well, as some countries from Latin America (Argentine, Colombia, and Peru). The whole experience was very productive and gratifying, being possible to present more informative content to the students. In addition, opens perspectives for a hybrid situation pos-pandemic phase.